BER performance simulation of rake receiver for WCDMA system - Lee, Li Ying (2007)
The goal for the next generation of mobile communications system is to seamlessly integrate a wide variety of communication services such as high speed data, video and multimedia traffic as well as voice signals. The technology needed to tackle the challenges to make these services available is popularly known as the Third Generation (3G) Cellular Systems. The received signal at the WCDMA Receiver Antenna subsystem is the sum of attenuated and delayed versions of the transmitted signals due to the so-called multi path propagation introduced by the channel. At the receiver side, a RAKE receiver is implemented to resolve and compensate for such effect. This project is mainly focus on the WCDMA concept and Rake receiver. In this project, bit error rate simulation was carried out to study different modulation techniques and the contribution of rake receiver in WCDMA system for the overall system performance. Next, evaluation on the bit error rate for rake receiver at different conditions such as varying number of rake fingers, spreading factor, type of channel (Additive White Gaussian Noise (AWGN) and Rayleigh Fading Channel) are carried out. Important parameters are selected and their influences on rake receiver performance are investigated by means of simulations. Performance improvement due to rake receiver important parameters are studied. This project was implemented by using Matlab Simulink 7.0. Bit-error-rate (BER) performance tradeoffs between spreading factor, type of channel, and the number of Rake fingers that can be exploited for other application other than mobile phones or wireless LAN are presented at the end of the project. The simulator developed is an invaluable tool for investigating the design and implementation of rake receiver in WCDMA systems and other possible applications.